2003
DOI: 10.1097/00045391-200301000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Release of a Keratinocyte Model After Incubation With Two Different Viscum album L Extracts

Abstract: When injected subcutaneously, extracts from the white berry mistletoe (Viscum album L) lead to a dose-dependent local inflammatory reaction at the injection site. From in vitro investigations with V album extracts, the release of proinflammatory cytokines from peripheral blood mononuclear cells and from a human skin model (Skin(2) model; Advanced Tissue Sciences, La Jolla, CA) is known. This shows dose dependence for mistletoe lectin-I in the range of 0.02 ng/mL to 10.0 ng/mL. In this study, an investigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In a skin model system, VAA-I (0.75–8 ng/ml) given in isolated form or in mistletoe extracts caused increased release of IL-1α and IL-6 dose dependently (44). In a model of multilayered keratinocytes, similar results were found (45). Proinflammatory cytokines play a significant role in the regulation of innate immunity.…”
Section: Biological Activity Of Mistletoe Lectin (Vaa-i)supporting
confidence: 78%
“…In a skin model system, VAA-I (0.75–8 ng/ml) given in isolated form or in mistletoe extracts caused increased release of IL-1α and IL-6 dose dependently (44). In a model of multilayered keratinocytes, similar results were found (45). Proinflammatory cytokines play a significant role in the regulation of innate immunity.…”
Section: Biological Activity Of Mistletoe Lectin (Vaa-i)supporting
confidence: 78%
“…European mistletoe lectin caused increased secretion of TNF-α, IL-1, and IL-6 in exposed human mononuclear cells (13). Experiments using multilayered skin keratinocytes showed that European mistletoe extracts caused the release of IL-1α, IL-2, IL-6, IL-10 and TNF-α (12). Thus, the present study suggests ML-J to have very similar properties to European and Korean mistletoe lectins so that ML-J can be expected to have anti-cancer activity in vivo.…”
Section: Effects Of Ml-j On Gene Expression In Caco-2 Cellssupporting
confidence: 54%
“…Conversely, the effects of different stimuli on the metabolic activity of macrophages and the secretion of proinflammatory mediators are clearly not superimposable [78,79]. It may also be the case that the secretion of proinflammatory mediators is increased after the inhibition of the metabolic activity of cells [80,81].…”
Section: Functional Properties Of Sst 1 and Sst 2 In Human Macrophagesmentioning
confidence: 98%